Monitoring of Gas Concentrations Dissolved in Transformer Oil During Operation of Power Transformer Equipment - Sakhno, O. A.; Domoroshchyn, S. V.; Skrupska, L. S. (Visnyk of Vinnytsia Politechnical Institute, 2021)
The peculiarities of application of stationary gas analyzers of power oil of filled equipment in main and distribution networks, as well as at power generation enterprises are analyzed. The problem of discrepancies in the values of concentrations of gases dissolved in oil obtained from stationary gas analyzers in the mode of continuous monitoring and obtained by the results of tests of transformer oil samples performed by laboratory chromatographers is investigated. A comparative analysis of different principles for measuring gas concentrations based on two groups of methods: chromatography method and infrared spectroscopy methods by Bouguer–Lambert–Beer law. The features of application, advantages and disadvantages of the main methods of infrared spectroscopy are considered. The results of the laboratory comparison of the analysis of the mixture of reference gases and the analysis of gases obtained from oil-filled transformer equipment, which is in operation, conducted by a stationary gas analyzer and laboratory. It is established that both laboratory devices and stationary gas analyzers have similar errors in determining gas concentrations in prepared laboratory mixtures. The coefficients of linear regression, constructed as a function of dependence of the indications of a stationary gas analyzer on the indications of a laboratory device, are given, when analyzing the same oil samples. Conclusions were made about the main reasons that affect the discrepancy of the obtained results, which allowed to determine the feasibility of using stationary gas analyzers, on the basis of spectroscopy, as devices capable of fixing the trend of increasing gas concentrations, and to make decisions on unscheduled oil samples for laboratory analysis based on their indications.